PENGARUH PANJANG SERAT DAN FRAKSI VOLUME TERHADAP SIFAT MEKANIK KOMPOSIT BERPENGUAT SERAT PANDAN DURI - Muhammad Nurdiansyah; Yuliyanto Yuliyanto; Sukanto Sukanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The development of polymer composite materials using natural fibers as a reinforcing medium is something that is necessary because it has many advantages. The study aimed to find out the values of tensile strength, modulus elasticity and optimum bending strength against fiber lengths of 60 mm, 80 mm, 100 mm and volume fractions of 5%, 10% and 15%. The highest tensile voltage is found at a fiber length of 100 mm with a fiber volume fraction of 15% which is 31.3 MPa,while the modulus elasticity of the highest tensile strength is found at a fiber length of 100 mm with a 15% seat volume fraction of 7150 Mpa. For the highest bending strength is found at a fiber length of 100 mm with a fiber volume fraction of 15% which is 66.8 MPa. And modulus values of strong elasticity bending with a fiber length of 100 mm with a fiber volume fraction of 15% 11500 MPa.